Strategi Pengembangan dalam Pemenuhan Konsumsi Pangan Sivitas Yayasan Permaculture - Eka Nurjati (Institut Pertanian Bogor, 2023)
Efforts to fulfill food consumption tend to pay little attention to ecosystem sustainability. Permaculture is an agricultural system that designs landscapes resembling natural ecosystems so that they can produce food and prioritize the principle of sustainability. However, as the population increases, permaculture must be reviewed to meet food consumption. This research is a case study in YS Permaculture that implements a permaculture farming system to meet the food consumption needs of the foundation's community. The purpose of the study is to identify the principles of permaculture in the empirical conditions of the foundation and formulate a development strategy to meet the food consumption of the foundation community. This research uses a qualitative descriptive method using an in-depth interview method with foundation management. Based on the identification of 12 permaculture principles, one principle still needs to be implemented optimally, namely, using and respecting renewable resources and their functions. Strategic steps that can be taken to increase the productivity of food commodities and fulfill food consumption are the extensification of permaculture gardens and the implementation of regenerative agriculture that integrates artificial intelligence, machine learning, and precision agriculture. The strategy of fulfilling food consumption for the foundation community through permaculture requires cooperation with various parties, including the government and academics, related to strengthening food security while still paying attention to environmental and social aspects. Keywords: environmental impact, food productivity, development strategy, permaculture, social impact